MAHMUD ZAMAHSHARI ABOUT MAFULLAR (Archive of Conferences, 2020)
The syntax of the Arabic language and its types, the primary and secondary parts of speech, were developed by medieval scholars, and are often quoted in the works of modern Arabic scholars. One such lifelong work is Mahmud Zamakhshari's Al-mufassal fi san'ati-l-i'rab and his abridged form for madrassas, Al-Unmuzaj fi-n-nahv.